Developing Early Childhood Emotional Intelligence by Organizing Storytelling Activities Accompanying Open-Ended Questions - Tang, ShuiMing; ์Nakunsong Thatsanee (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Early childhood emotional intelligence is a result of the child’s experiences in the environment. Storytelling is a simple form of recreation that satisfies the natural needs of humans, allows for mutual learning, and can take listeners into a world of imagination. The listener will find something new and fun to temporarily escape from the monotony of everyday life. Sometimes stories help explain various phenomena that occur in the world. Developing the emotional intelligence of early childhood children by organizing storytelling activities with open-ended questions. The objective was to compare the emotional intelligence of early childhood children before and after organizing storytelling activities with open-ended questions. Methodology: The sample group includes 15 early childhood children aged 5-6 years who are studying in Kindergarten 3, Semester 1, Academic Year 2023, Guangxi Kindergarten School, Guangxi Province, China, obtained by purposive sampling. The tools used in the research include: There were 8 plans for organizing storytelling activities with open-ended questions. The suitability of the plans was at the most appropriate level and the early childhood emotional intelligence assessment form had 10 questions. The consistency value was 0.80-1.00. Statistics used in the analysis Data includes mean, and standard deviation. Results: the research results found that Early childhood children after receiving the storytelling activity with open-ended questions had higher emotional intelligence than before the activity. Conclusion: the value of stories will help enhance development in various areas. Especially promoting emotional intelligence very well. Therefore, when teachers tell stories, they should ask open-ended questions and allow children to think of multiple answers, which will have a great impact on the emotional intelligence of early childhood.